2018
DOI: 10.1016/j.physbeh.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous GLP-1 in lateral septum contributes to stress-induced hypophagia

Abstract: Glucagon-like peptide 1 (GLP-1) neurons of the caudal brainstem project to many brain areas, including the lateral septum (LS), which has a known role in stress responses. Previously, we showed that endogenous GLP-1 in the LS plays a physiologic role in the control of feeding under non-stressed conditions, however, central GLP-1 is also involved in behavioral and endocrine responses to stress. Here, we asked whether LS GLP-1 receptors (GLP-1R) contribute to stress-induced hypophagia. Male rats were implanted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
5
24
1
Order By: Relevance
“…In the rat, we have previously reported that GLP-1R blockade in the dorsal subregion of the LS (dLS) significantly attenuates stress-induced hypophagia [27]. Here, we utilized a mixedmodel design to assess the feeding response to stress in intra-dLS saline and Ex9-treated mice.…”
Section: Study 4: Effects Of Dls Glp-1r Blockade On Stress-induced Hymentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat, we have previously reported that GLP-1R blockade in the dorsal subregion of the LS (dLS) significantly attenuates stress-induced hypophagia [27]. Here, we utilized a mixedmodel design to assess the feeding response to stress in intra-dLS saline and Ex9-treated mice.…”
Section: Study 4: Effects Of Dls Glp-1r Blockade On Stress-induced Hymentioning
confidence: 99%
“…Because the LS has a known role in stress responses [25,26], we investigated the contribution of LS GLP-1R. We reported that in rats, intra-dLS pretreatment with low-dose GLP-1R antagonist attenuated restraint stress-induced hypophagia [27]. Much of the research described above was conducted in rats, and the work that has been done in mice reveals some similarities and several notable species differences.…”
Section: Introductionmentioning
confidence: 99%
“…). Finally, blocking GLP‐1R signaling in LS attenuates stress‐induced suppression of feeding (Terrill, Maske, & Williams ). Therefore, it is unclear if changes in drug seeking following LS manipulations are due to alterations in reward or anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…7 C, D; p=0.0013 and p=0.0004, respectively). Because GLP-1 is involved in the regulation of stress and anxiety (Tauchi et al, 2007;Terrill et al, 2018), we also tested whether re-expression of LepRb on PPG neurons regulates anxiety-like behavior by performance on the elevated zero maze. As expected, LepRb TB/TB mice displayed increased anxiety-like behaviors by increased percent of time spent in the closed arm (Fig.…”
Section: Targeted Expression Of Leprb On Ppg Neurons Does Not Normalimentioning
confidence: 99%